2023
DOI: 10.1021/acs.orglett.3c02292
|View full text |Cite
|
Sign up to set email alerts
|

Photoinduced Nitroarenes as Versatile Anaerobic Oxidants for Accessing Carbonyl and Imine Derivatives

Joshua K. Mitchell,
Waseem A. Hussain,
Ajay H. Bansode
et al.

Abstract: Herein, we report a protocol for the anaerobic oxidation of alcohols, amines, aldehydes, and imines promoted by photoexcited nitroarenes. Mechanistic studies support the idea that photoexcited nitroarenes undergo double hydrogen atom transfer (HAT) steps with alcohols and amines to provide the respective ketone and imine products. In the presence of aldehydes and imines, successive HAT and oxygen atom transfer (OAT) events occur to yield carboxylic acids and amides, respectively. This transformation is amenabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 46 publications
0
6
0
Order By: Relevance
“…The ability of photoexcited ni-troarenes to yield oxygen atom transfer reactions was further investigated to furnish a variety of oxidized products in later studies. 56,57 A contemporaneous study by Leonori, Simonetti, and co-workers was also reported (Scheme 13). 58 The methodology is similar to Parasram's protocol in featuring the cleavage of alkenes promoted by electron-deficient nitroarenes.…”
Section: Short Review Synthesismentioning
confidence: 90%
See 1 more Smart Citation
“…The ability of photoexcited ni-troarenes to yield oxygen atom transfer reactions was further investigated to furnish a variety of oxidized products in later studies. 56,57 A contemporaneous study by Leonori, Simonetti, and co-workers was also reported (Scheme 13). 58 The methodology is similar to Parasram's protocol in featuring the cleavage of alkenes promoted by electron-deficient nitroarenes.…”
Section: Short Review Synthesismentioning
confidence: 90%
“…Interestingly, trans-stilbene derivatives led to diketone formation 55 instead of the cleavage product owing to the reduced reactivity of the highly conjugated starting material. The authors nicely illustrated that their protocol is amenable to late-stage functionalization of medicinally relevant molecules (56,57).…”
Section: Photopromoted Organocatalyzed Oxidative Cleavage Of Alkenesmentioning
confidence: 99%
“…In 2023, Parasram [38] disclosed an anaerobic oxidation strategy involving alcohols, aldehydes, and imines, facilitated by photoexcitable nitroarenes (Scheme 18). The methodology demonstrates robust substrate compatibility, particularly with trifluoromethyl and cyano-substituted alcohols, yielding the respective ketones in high yields of 70 % and 98 % (115 a, 115 b).…”
Section: The Photo-induced Nitroarene Promoted Oxidationmentioning
confidence: 99%
“… 27 These initial reports set the stage for additional developments such as the dihydroxylation of alkenes, 28 hydroxylation of aliphatic substrates, 29 and the oxidation of aldehydes and aldimines to carboxylic acids and amides, respectively. 30 Furthermore, Li recently reported a photoinduced cascade process between nitroarenes and amines to form isoxazolidine derivatives. 31 …”
Section: Introductionmentioning
confidence: 99%